Enhanced thermoelectric properties of the flexible tellurium nanowire film hybridized with single-walled carbon nanotube - Choi, Jaeyoo; Lee, Jang Yeol; Lee, Hyunjung; Park, Chong Rae; Kim, Heesuk (ELSEVIER SCIENCE SA, 2014)
Thermoelectrics is a challenging issue for future energy harvesting and cooling technology. We here have demonstrated a new system of the tellurium nanowire (TeNW) films hybridized with single-walled carbon nanotube (SWCNT) as a flexible thermoelectric material and investigated their thermoelectric properties as a function of SWCNT weight ratio in the hybrid. The excellent mechanical stability and electrical conductivity of SWCNT enhance the flexibility and thermoelectric properties of the pure TeNW film. The addition of 2 wt% SWCNT into TeNW matrix significantly increases the electrical conductivity from 4 to 50 S m(-1) while maintaining the high thermopower, thereby leading to one order of magnitude higher figure of merit (ZT) compared to the pure TeNW film. These results indicate that the SWCNT/TeNW hybrid film would be promising for a potential use as a flexible thermoelectric material. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: ORGANIC COMPOSITES; POWER; THERMOPOWER; PERFORMANCE